The last life of Prince Alastor - Bracken, Alexandra (Disney-Hyperion, 2019)
Prosper Redding is determined to save his sister from the evil queen Pyra even if it means promising eternal servitude to the malefactor within him. Accomplishing his mission will mean partnering with Prince Alastor, heir of the demon kingdom. But with Pyra in control, even the fate of the demons could be at stake.